Potential of trichloroacetic acid (TCA) for cervical precancerous lesions treatment in Indonesia - I Gde Sastra Winata; Musa Taufiq (Majalah Obstetri dan Ginekologi, 2022)
HIGHLIGHTS 1. One of the most prevalent disease in females worldwide is cervical cancer.2. Simple and safe modality with high efficacy to treat cervical precancerous lesions before being progressed to cancer is necessary. 3. Trichloroacetic acid (TCA) has those advantages, so it will become an effective treatment for cervical precancerous lesions in the future.   ABSTRACT Cervical cancer becomes one of the most prevalent disease in female worldwide. Human papillomavirus (HPV) is main etiology of cervical cancer, thus this disease is preventable. Before progressed into invasive cervical cancer, cervical precancerous lesions developed and classified into 3 stages: CIN1 (LSIL), CIN2, and CIN3 (CIN2+ also referred as HSIL). World Health Organization (WHO) arranged ‘screen-and-treat’ programme to treat cervical precancerous lesions immediately before it progressed to cancer. However, a simple and safe modality with high efficacy is necessary to accommodate this strategy. Trichloroacetic acid (TCA) has those advantages and some research suggested high efficacy to treat cervical precancerous lesions with simple, safe, and cost-effective. TCA has potential to become effective treatment for cervical precancerous lesions in the future.